A TWO YEARS AUDIT OF COMPLICATIONS OF HYSTERECTOMY AT AYUB TEACHING HOSPITAL ABBOTTABAD - Bashir, Rubina; Parveen, Zahida; Sultana, Ruqqia; Khan, Bushra (Journal of Ayub Medical College Abbottabad, 2005)
Background: Hysterectomy is one of the most common major surgical procedures performed in Gynaecology. Our objective was to determine the operative and postoperative complications of this procedure with an aim to improve management at our unit. Methods: This study was conducted in the Department of Gynaecology, Ayub Teaching Hospital, Abbottabad form January 2002 to December 2003. Indications, complications and mortality associated with hysterectomy were assessed. Results: Total number of hysterectomies performed in two years at our unit was 316. Major Indications for hysterectomies were dysfunctional uterine bleeding (38%) and fibroid uterus, (27%) followed by prolapse (22%). Complications developed in 14% out of these. The frequency of complications was related with indication for hysterectomy, age, parity and history of associated serious illness. It was found that frequency of complications in fibroid uterus was higher (1.2%) than that for Dysfunctional uterine bleeding (DUB) (1.0%). There was no operative death, while 5 (1.5%) patients died within 2 weeks of surgery. Conclusion: We have a fairly high frequency of morbidity and mortality associated with hysterectomy. In order to reduce these proper selection, pre-operative preparation and less invasive alternative treatment for the commonest indications of hysterectomy (that is fibroids and DUB) for example various methods of endometrial ablation or resections can be employed. Keywords: Hysterectomy, Complications, morbidity, dysfunctional uterine bleeding